Building Organizational Capabilities to Adapt under Turmoil - Pettigrew, A; Hatum, A; Michelini, J (2010)
This article uses two case studies of family-owned firms to assess the organizational capabilities necessary for survival under conditions of environmental volatility. Both organizations belong to the edible oil industry and are among Argentina’s leading oilseed processors and exporters. The most-adaptable firm undertook transformations involving continuous change, while the less-adaptable firm displayed a more revolutionary attempt at transformation. The outcome of the transformation process in the most-adaptable firm does not conform to patterns portrayed in the literature on adaptation and change, which involve long periods of stability or convergence and short periods of revolutionary change. We find that the life-cycle of family firms, the role of the founder, control systems and the professionalization of the management team, and ownership issues most strongly influence the capabilities of these firms.